PENGARUH KEPEMIMPINAN, KOMUNIKASI, KOMPETENSI, DAN TINGKAT PENDIDIKAN TERHADAP KINERJA PEGAWAI DI DINAS PENDIDIKAN KABUPATEN WONOGIRI - -, Tariyo -; -, Mulyanto - (Universitas Slamet Riyadi, 2012)
ABSTRACT The aim of this research are to test the influences of the leadership, the communication, and competense on the performance of officers with the motivation as a moderating variable at Dinas Pendidikan Kabupaten Wonogiri. Data was collected from 50 officers as a sample. It was collected directly with a questioner and observation. The result of the this research prove that equation of double linear regression shows: The t test also prove that the leadership positive and significant on the performance of officers at Dinas Pendidikan Kabupaten Wonogiri. The communication influential positive and significant on the performance of officers at Dinas Pendidikan Kabupaten Wonogiri. The competense influential positive and not significant on the performance of officers at Dinas Pendidikan Kabupaten Wonogiri. The education influential negative and not significant on the performance of officers at Dinas Pendidikan Kabupaten Wonogiri. The motivation influential positive and significant on the performance of officers at Dinas Pendidikan Kabupaten Wonogiri.. F test or simultaneous the leadership, the communication, and competense, and the motivation on the performance of officers at Dinas Pendidikan Kabupaten Wonogiri. Determination test (R2 test) shows that dependent variable can be cleared by the leadership, the communication, and competense that be researched for the fist and second of equation of double linear regression about 91,7% and (8,3%) be cleared out side of variable. The motivation didn’t moderate the influence of the leadership, the communication, and competense and education on the performance of officers at Dinas Pendidikan Kabupaten Wonogiri. Keywords: the leadership, the communication, and competense, and the motivation and the performance